Flash CS4 for dummies - Finkelstein, Ellen; Leete, Gurdy; Safari eBooks (Hoboken, N.J. : Wiley Pub., 2008)
"With Adobe Flash CS4 For Dummies as your guide, you can unleash your creativity and contribute to the "Flash"-iest showcase of dynamic content: the Web! You'll become acquainted with Flash CS4 and learn when to use this popular Web development tool. Plus, you'll discover what you can create, from animation to games to presentations. This full color edition gives you the opportunity to get acquainted with Flash CS4, discover all the possibilities, and become familiar with the new tools. You'll be able to create dynamic content, adapt the program's features to suit your development needs, publish your Flash files to the Web, and showcase your creativity and newly acquired skills. You'll discover how to create graphics, text, and layers, make animations, add sound and video, and optimize your files for download"--Resource description page.
Getting acquainted with Flash CS4 -- Your basic Flash -- Getting graphic -- You are the object editor -- What's your type? -- Layering it on -- Heavy symbolism -- Pushing buttons -- Getting animated -- Getting interactive -- Extravagant audio, high-velocity video -- Putting it all together -- Publishing your Flash files -- Ten frequently asked questions -- Ten best Flash resources -- Ten Flash designers to watch.
Description based on print version record.
Includes index.
Keywords: Flash (Computer file); Computer animation; Web sites -- Design; ActionScript (Computer program language); Electronic books